A benchmark study of the material models for forming simulation of woven fabrics. Issue 6 (3rd June 2022) - Yildirim, Halil; Ozturk, Fahrettin
Abstract: Large amounts of angular distortions occur during the forming of woven fabrics. It is extremely important to predict the angular distortions during the forming since they determine the mechanical response of the formed product. In this regard, finite element analysis (FEA) is an effective approach to predict the forming behavior of woven structures, and thus in this work an FEA simulation of a hemispherical forming process is studied by using the Viscoelastic Loose Fabric Model (MAT_234), Micromechanics Dry Fabric Model (MAT_235), and Anisotropic Hyperelastic Model (MAT_249), which are three commonly used models in LS-DYNA material library for modeling of woven structures. The results reveal that the Viscoelastic Loose Fabric Model (MAT_234) and Anisotropic Hyperelastic Model (MAT_249) provide accurate results in terms of outer contour and shear angle distribution of deformed fabric, whereas the Micromechanics Dry Fabric Model (MAT_235) fall behind these two models in terms of prediction capability.